2015
DOI: 10.1515/geochr-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

The oldest seafloor massive sulfide deposits at the Mid-Atlantic Ridge: <sup>230</sup>Th/U chronology and composition

Abstract: A geochronological and geochemical study on 10 samples of seafloor massive sulfides (SMS) from the inactive Peterburgskoye hydrothermal field at the Mid-Atlantic Ridge (MAR) was carried out. The 230 Th/U ages of the SMS are the oldest for the Quaternary hydrothermal ores ever found at the ocean floor. According to them the hydrothermal activity at Peterburgskoye field started at least 170 ka and continued down to 63 ka. The oldest hydrothermal ores from this field consist mainly of pyrite and chalcopyrite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The samples with low U contents yield some of the older ages as well as younger ages. The U contents of sample 34-T8-1-1 (64.60 ± 0.12 ppb), 34-T8-1-2 All these excludes open system conditions with respect to uranium (Lalou et al 1998b;Kuznetsov et al 2015;Mills et al 1994). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples with low U contents yield some of the older ages as well as younger ages. The U contents of sample 34-T8-1-1 (64.60 ± 0.12 ppb), 34-T8-1-2 All these excludes open system conditions with respect to uranium (Lalou et al 1998b;Kuznetsov et al 2015;Mills et al 1994). …”
Section: Resultsmentioning
confidence: 99%
“…While the ESR (electron spin resonance) dating of barite ( 226 Ra/ 228 Ra) in seafloor hydrothermal fields can obtain ages of 300-3620 years (Kasuya et al 1991;Okumura et al 2010). So far, the 230 Th/ 238 U dating was used to obtain the ages of seafloor massive sulfide deposits from the East Pacific Ridge (EPR), the Mid-Atlantic Ridge (MAR) and the Central Indian Ridge (CIR) (Lalou and Brichet 1982, 1988, 1998aYou and Bickle 1998;Kuznetsov et al 2006Kuznetsov et al , 2007Kuznetsov et al , 2011Kuznetsov et al , 2013Kuznetsov et al , 2015Münch et al 1999;Wang et al 2012). The limited data established Trans-Atlantic Geotraverse (TAG) as one of the longest-lived active vent field with a maximum age of 50 kyrs (Lalou et al 1995;You and Bickle 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Uranium and thorium were radiochemically extracted from the samples by applying the procedure described earlier by Kuznetsov et al (2006Kuznetsov et al ( , 2015. The specific 238 U, 234 U, 232 Th and 230 Th activities were measured over several days using the alpha-spectrometer "Alpha Duo" (ORTEC).…”
Section: Materials and Analytical Methodsmentioning
confidence: 99%
“…Th/U ages of sulfide ores were obtained by Lalou et al (1986Lalou et al ( , 1993Lalou et al ( , 1996 for the samples from hydrothermal fields at the Mid-Atlantic Ridge (MAR). Since that time, numerous data were obtained by the 230 Th/U, 210 Pb and 226 Ra/Ba methods for hydrothermal deposits at the MAR, East Pacific Rise, South-West Indian Ridge and other ridges and Island Arc systems (Lalou et al, 1998;You and Bickle, 1998;Kuznetsov et al, 2006Kuznetsov et al, , 2007Kuznetsov et al, , 2011Kuznetsov et al, , 2015Kuznetsov and Maksimov, 2012;Wang, 2012;Jamieson et al, 2013;Yang et al, 2017;Cherkashov et al, 2017;Liang et al, 2018). It was shown that the hydrothermal activity and the related ore formation had a pulse pattern marked by a certain number of episodes recurring with time intervals up to several thousand years.…”
mentioning
confidence: 99%
“…The age of the Ashadze-1 field is estimated as less than 7.1 kyr (Table 5), whereas most hydrothermal fields on the MAR are much older, up to 170 kyr [26]. The Ashadze-1 deposit is considered an example of a hydrothermal system in its initial stage of evolution marked by the young age of the sulfides (<7.2 kyr).…”
mentioning
confidence: 99%